2020
DOI: 10.1186/s40729-020-00273-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between risk markers for cardiovascular disease and peri-implant diseases

Abstract: Background The aim of this paper is to explore the serum biochemical parameters also known as risk markers for cardiovascular system, in individuals who have received dental implant treatment, and to reveal risk factors for peri-implant diseases. Methods The study included 58 subjects with peri-implantitis, 49 subjects with peri-implant mucositis, and 49 healthy subjects. All the subjects were assessed in terms of both peri-implant clinical paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 57 publications
2
28
0
1
Order By: Relevance
“…Actually, serum inflammatory markers resulted higher in dogs with experimental peri-implantitis in another study by the same authors [ 39 ]. One recent human study reinforced this evidence, finding that common CVD markers such as triglycerides, uric acid, and white blood cells were significantly higher in patients with peri-implantitis [ 40 ].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Actually, serum inflammatory markers resulted higher in dogs with experimental peri-implantitis in another study by the same authors [ 39 ]. One recent human study reinforced this evidence, finding that common CVD markers such as triglycerides, uric acid, and white blood cells were significantly higher in patients with peri-implantitis [ 40 ].…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, another recent study [ 40 ] measured serum biochemical parameters that are known as CVD markers in patients affected by peri-implantitis, which resulted to show significantly higher levels of triglycerides, uric acid, and white blood cells as compared to healthy subjects or patients affected by peri-mucositis. They also had the lowest levels of vitamin D. The authors found a positive correlation between uric acid, triglyceride, and gingival index, pocket depth, bleeding on probing, and the amount of keratinized mucosa around the implants.…”
Section: The Impact Of Peri-implantitis On Systemic Conditionsmentioning
confidence: 99%
“…The relationship between cardiovascular diseases and periodontitis has been reported in many studies in the literature 5–7 . Due to pathophysiological similarities between peri‐implantitis and periodontitis, peri‐implantitis may also be associated with systemic inflammation and cardiovascular diseases 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…Apart from the already known collateral problems (metabolic syndrome (MetS), cardiovascular disease (CVD), Alzheimer’s disease, etc.) of peri-implant disease [ 16 , 17 , 18 ], very recently, the relationship between this disease and greater severity of COVID-19 has been reported [ 19 ]. Marouf et al [ 19 ] reported that patients with periodontitis are nine times more likely to die from COVID-19 than those without it.…”
Section: Introductionmentioning
confidence: 99%